About the plume rise description in the dispersion code SAFE_AIR. (1st January 2000) - Canepa, E.; Dallorto, L.; Ratto, C.F.
SAFE_AIR is a code simulating the transport and diffusion of airborne pollutants. This code is based on the advection of Gaussian segments and puffs driven by a 3-D wind field produced by a diagnostic model, able to deal with both non-stationary and inhomogeneous conditions. SAFE_AIR is an evolution of the AVACTA II code, "recommended" by the US EPA (United States Environmental Protection Agency). We have recently revised the simulation of the plume rise phenomenon. We have evaluated this last version of the SAFE_AIR code against the Kincaid dataset; here we present the results obtained using both the plume rise formulae recommended by Briggs and the plume rise Moore model; the interaction between the rising of the plume and the top of the mixed layer is also taken into account.